Compositional dependence of optical properties of zirconium, hafnium and tantalum carbides for solar absorber applications. (June 2016) - Sani, Elisa; Mercatelli, Luca; Meucci, Marco; Balbo, Andrea; Silvestroni, Laura; Sciti, Diletta
Highlights: Zr, Hf and Ta carbides with 10% and 20% MoSi2 are produced for solar absorbers. Structural, optical and mechanical characteristics are comparatively assessed. 10%-added samples typically have better fracture strength and optical properties. TaC shows superior mechanical and optical performance than HfC and ZrC. Abstract: Besides ultra-refractoriness and favorable mechanical and chemical characteristics, carbides of early transition metals show intrinsic spectral selectivity, making them appealing for high-temperature solar absorber applications. However these kinds of ceramics can be produced using many processing methods resulting in different compositions, density and surface finishing. Thus the present work reports on the systematic study of microstructural, mechanical and optical properties of dense zirconium, hafnium and tantalum carbides as a function of the sintering method (high pressure or pressureless), implying use of 10 or 20 vol% of MoSi2 as sintering aid. The spectral hemispherical reflectance of Zr-, Hf- and Ta-carbides has been measured in the 0.25–16.5 μm wavelength range and correlated to the surface microstructure and roughness. Room and high temperature fracture strength has been measured as well.